2004
DOI: 10.1021/jp049759d
|View full text |Cite
|
Sign up to set email alerts
|

Products and Mechanisms of Ozone Reactions with Oleic Acid for Aerosol Particles Having Core−Shell Morphologies

Abstract: Heterogeneous reactions of oleic acid aerosol particles with ozone are studied below 1% relative humidity. The particles have inert polystyrene latex cores (101-nm diameter) coated by oleic acid layers of 2 to 30 nm. The chemical content of the organic layer is monitored with increasing ozone exposure by using an aerosol mass spectrometer. The carbon-normalized percent yields of particle-phase reaction products are 20-35% 9-oxononanoic acid, 1-3% azelaic acid, 1-3% nonanoic acid, and 35-50% other organic molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
299
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(339 citation statements)
references
References 52 publications
34
299
2
1
Order By: Relevance
“…Our partitioning results for the oleate O 3 oxidation products in mixed aqueous salt particles are in qualitative agreement with those of Hearn and Smith 37 and Katrib et al, 46 who observed that nonanoic acid, 9-oxononanoic acid, and azelaic acid are present in the condensed phase after ozone oxidation of pure . Temperature-programmed desorption study of O3 oxidation product volatility.…”
Section: Results Andsupporting
confidence: 91%
See 3 more Smart Citations
“…Our partitioning results for the oleate O 3 oxidation products in mixed aqueous salt particles are in qualitative agreement with those of Hearn and Smith 37 and Katrib et al, 46 who observed that nonanoic acid, 9-oxononanoic acid, and azelaic acid are present in the condensed phase after ozone oxidation of pure . Temperature-programmed desorption study of O3 oxidation product volatility.…”
Section: Results Andsupporting
confidence: 91%
“…This is consistent with the mechanisms proposed by other investigators that include reaction of oleic acid with the Criegee biradical in pure oleic acid particles. 37,39,43,46 The ozone oxidation products that we are able to observe using CIMS with I -as a reagent ion (nonanoic acid, 9-oxononanoic acid, and azelaic acid) were associated with the particle phase at ambient temperature. A temperature-programmed desorption experiment was performed to investigate the gas-particle partitioning of the ozone oxidation products.…”
Section: Results Andmentioning
confidence: 95%
See 2 more Smart Citations
“…The reaction of oleic acid (cis-9-octadecenoic, 9C 18 ) with O 3 , OH and NO 3 has recently emerged as a model system to better understand the photooxidation processes affecting unsaturated fatty acids in atmospheric aerosols [11,12]. Oleic acid is degraded through an oxidative cleavage of its double bond to produce C 9 compounds, i.e., nonanoic (C 9 ), 9-oxononanoic (ωC 9 ) azelaic (C 9di ) acids and 1-nonanal (C 9ald ) [13,14,15,16] as well as nitrated carboxylic acids [12]. Secondary photooxidation reactions could initiate the production of lower molecular weight DCAs such as C 2di -C 8di [9,17,18].…”
Section: Introductionmentioning
confidence: 99%